Clinical Characteristics and Management of Wet Age-Related Macular Degeneration at Cipto Mangunkusumo Hospital Kirana, Jakarta, Indonesia - Leonedine, Tengku Viona Zohra; Victor, Andi Arus; Djatikusumo, Ari; Adriono, Gitalisa Andayani; Yudanta, Anggun Rama; Hutapea, Mario Marbungaran; Suryoadji, Kemal Akbar (International Journal of Retina, 2024)
Introduction: Age-related macular degeneration (AMD) is a leading cause of blindness globally, with wet AMD being particularly debilitating. The prevalence of AMD is increasing, necessitating a deeper understanding of its clinical characteristics and management. This study aims to investigate the demographic and clinical features, management, and treatment outcomes of wet AMD at Cipto Mangunkusumo Hospital during January-December 2022. Methods: A retrospective descriptive study was conducted, analyzing medical records of wet AMD patients treated during the specified period. Data analysis included patient demographics, clinical characteristics, treatment modalities, and outcomes. Results: Of 129 eyes from 122 patients, 115 eyes met the inclusion criteria. The majority were female (55.7%) with an average age of 67 years. Most patients presented with blurry vision (93.9%) and received Patizra anti-VEGF injections (60.9%). Hypertension was the most common risk factor (28.7%). Anti-VEGF treatment significantly reduced central macular thickness (p < 0.05) but had no significant impact on visual acuity. Avastin and Patizra injections similarly influenced macular thickness but not visual acuity. There were no significant differences between loading and non-loading dose groups in terms of outcomes. Conclusion: Anti-VEGF treatment effectively reduces central macular thickness in wet AMD patients, regardless of the specific agent used. However, it does not significantly improve visual acuity. Further research is needed to explore differences between loading and non-loading dose protocols, compare treatment strategies, and investigate demographic risk factors. Consistency in visual acuity documentation using the ETDRS format is recommended for future studies.